Religion Et Transition Énergétique : Une Étude en Amérique Du Sud - Parker-Gumucio, C (SAGE Publications Ltd, 2015)
Global society’s goal is to transition to more sustainable forms of energy production and consumption. How is the religious factor supporting this transition to sustainable energy models and renewable energy? This is a question that social scientists are only just beginning to respond to. In Latin America, it has hardly been raised. This article is an effort to answer this question, taking into account the complex nature of the definition of religion and religiosity. Building on a mixed methodology, the author analyses a national survey of Chilean university students. He observes the relationship between religiosity or declared religious choice and certain aspects of the energy transition – energy efficiency, renewable energy and social patterns of sustainable energy consumption – and finds that religion does play a role, but that this is heterogeneous: many trends indicate that Catholics, evangelicals and members of missionary churches do not support the energy transition, while non-believers do, but the trends are weak. The author analyses these and other trends, ponders their meanings and provides an interpretation and typology. His interpretation points to the need for further study of the relationship between religion and changing lifestyles towards more sustainable forms of energy. © 2015, © The Author(s) 2015.